2013
DOI: 10.1371/journal.pone.0082299
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Caffeic Acid Phenethyl Ester Derivatives on Replication of Hepatitis C Virus

Abstract: Caffeic acid phenethyl ester (CAPE) has been reported as a multifunctional compound. In this report, we tested the effect of CAPE and its derivatives on hepatitis C virus (HCV) replication in order to develop an effective anti-HCV compound. CAPE and CAPE derivatives exhibited anti-HCV activity against an HCV replicon cell line of genotype 1b with EC50 values in a range from 1.0 to 109.6 µM. Analyses of chemical structure and antiviral activity suggested that the length of the n-alkyl side chain and catechol mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 40 publications
0
26
1
Order By: Relevance
“…Recently, it was reported that CA prevented HCV genome replication, 13,14) but we did not observe this effect in the present study (Fig. 2).…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…Recently, it was reported that CA prevented HCV genome replication, 13,14) but we did not observe this effect in the present study (Fig. 2).…”
Section: Discussioncontrasting
confidence: 90%
“…This might be explained by differences in researchers' use of host cells and viral/replicon strains. In the present study, we used Huh7.5.1-8 cells and HCV-JFH1 (genotype 2a), while previous studies have used Huh7, 13,14) Huh7.5.1, 13) Con1 replicon (genotype 1b), J399EM (genotype 2a), a JFH-1-based adaptive strain in which an enhanced green fluorescent protein (EGFP) gene was inserted into NS5A, 13) and N replicon (genotype 1b). 15) It has also been reported that CA has inhibitory effects on other viruses such as hepatitis B virus (HBV), canine distemper virus (CDV), herpes simplex virus type 1 (HSV-1), influenza A virus (IAV), polio virus type 1 (PV-1), and severe fever with thrombocytopenia syndrome virus (SFTSV) in cultured cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, a broad spectrum of biological properties in addition to antitumor and anti‐inflammatory activities has been reported for CAPE. For example, CAPE was recently reported with inhibitory effects on replication of hepatitis C virus . We believe that the inhibition of nuclear export by CAPE is a rather reasonable explanation for its various biological activities.…”
Section: Discussionmentioning
confidence: 72%